Establishing and researching school gardens in Oman as a resource for improving education and health outcomes - Abdullah Ambusaidi; Rashid Al-Yahyai; Neil Taylor (Economic and Environmental Studies (E&ES), 2015)
Like many other countries where the standard of living is rising, the Sultanate of Oman is facing a potentially serious increase in what are now termed "ifestyle" diseases. These include diabetes, heart disease, hypertension and various forms of cancer. The lifestyle factors that contribute to these diseases are poor diet and limited exercise. A school gardening project being implemented in Oman is intended to improve educational outcomes across the curriculum in the short term but also dietary outcomes in the longer term. If successful the project will be expanded to a much larger number of schools in Oman. In a country that imports much of its fruit and vegetables there are also potential, long-term economic benefits in encouraging the local production of these food items. This article reports on the rationale behind this project and its overall conceptualization and design. The project is funded through the Oman Research Council.
Keywords: I15; 330; Oman; school gardening; "lifestyle" diseases; curriculum; quasi-experimental design; imports